Correlation of electrolytes with falling risk, cognitive function, and functional outcome in acute ischemic stroke patient - Mirawati, Diah Kurnia; Ristinawati, Ira; Prabaningtyas, Hanindia Riani; Tedjo, Raden Andi Ario; Putra, Stefanus Erdana; Hafizhan, Muhammad; Ilhamsyah, Rudi (International Journal of Public Health Science (IJPHS), 2024)
Stroke outcome is determined on multiple factors. However, there are limited studies discussing the impact of electrolyte imbalance on stroke outcome. In this study, we analyzed sodium, calcium, and potassium level in acute ischemic stroke, and compare their risk of falling, cognitive function, and functional outcome. This was a cross-sectional study in Dr. Moewardi General Hospital, Indonesia between January and June 2023. Patient with acute ischemic stroke were enrolled in this study. Cognitive function was assessed with mini mental state examination (MMSE) and the Indonesian version of montreal cognitive assessment (MoCA-Ina). National Institutes of Health Stroke Scale (NIHSS), Modified Rankin Scale (MRS) and Morse Fall Score (MFS) were used to assessed stroke severity, disability, and risk of falling, respectively. Pearson correlation was then performed to evaluate the correlation of electrolytes level with MMSE, MoCA-Ina, NIHSS, MRS, and MFS. Furthermore, we also analyzed the odds ratio of increasing risk of falling, cognitive function deterioration, and worse functional outcome. A p-value of <0.05 is considered statistically significant. On univariate analysis, natrium is correlated with MMSE (r=0.174; p=0.042), NIHSS (r=-0.412; p=0.011), MRS (r=-0.174; p=0.042), and MFS (r=-0.304; p=0.042). Potassium is correlated with MMSE (r=0.344; p=0.044), MoCA-INA (r=0.341; p=0.048), NIHSS (r=-0.572; p=0.019), (MRS r=-0.376; p=0.017), and MFS (r=-0.612; p=0.031). Calcium is correlated with NIHSS r=-0.348 (p=0.018), MRS r=-0.256 (p=0.036). On odds ratio analysis, low natrium level increased the risk of deteriorating cognitive function, and low level of potassium increased the risk of falling. Electrolyte imbalances correlates with risk of falling and deteriorating cognitive function.